'Like a family in the end': Improving mental health Recovery skills through Peer‐to‐Peer communication in Darwin, Australia. (10th August 2022) - Tari‐Keresztes, Noemi; Girdler, Xenia; Gupta, Himanshu; Clarke, Brendon; Christie, Ben; A. Smith, James; Armstrong, Noelene; Harris, Vanessa
Abstract: The existing psychosocial Support activities in the Northern Territory, Australia, are mostly delivered through individualised outreach and client‐centred Support programs and do not currently have a strong Peer focus. To address this gap, a Peer‐Led Education Pilot was developed and implemented in Darwin, Australia. The pilot was comprised of three separate but overarching stages, and each stage was independently evaluated. In this article, results from Stage 1 will be presented, with a specific focus on the role of Peer‐to‐Peer communication in improving participants' mental health and Recovery skills. This stage involved the delivery of the My Recovery program to self‐nominated participants, and the evaluation was aimed at reporting on the appropriateness and effectiveness of the program. The evaluation was qualitative in design involving individual pre‐ and post‐program interviews with program participants ( n pre = 14, n post = 16) between August and October 2019. The program was well received by participants and helped build their capacity to understand and self‐manage their mental health and/or alcohol and other drug issues in an inclusive, non‐clinical, non‐judgemental space. The results highlighted the importance of including a strong Peer focus in the existing psychosocial Support services available for people with mental health issues in Darwin. The findings also underscored the inclusion of those with lived experience of mental health challenges in the design and delivery of such programs.